A versatile luminescent resonance energy transfer (LRET)-based ratiometric upconversion nanoprobe for intracellular miRNA biosensing. Issue 27 (17th June 2020) - Gong, Liang; Liu, Simin; Song, Ya; Xie, Shaowen; Guo, Ziyu; Xu, Jianxiong; Xu, Lijian
Abstract : A versatile LRET-based ratiometric (LBRU) nanoprobe of NaYF4 :Yb, Er@NaYF4 @NH2 –mSiO2 /rhodamine B/C-DNA sandwich-structured nanocomposites has been developed for intracellular miRNA biosensing. Abstract : Rational design and fabrication of bio-nanoprobes for intracellular miRNA biosensing are highly desired for early clinical diagnosis and prognosis. Herein, we have developed a versatile LRET-based ratiometric (LBRU) nanoprobe of NaYF4 :Yb, Er@NaYF4 @NH2 –mSiO2 /rhodamine B/C-DNA sandwich-structured nanocomposites for intracellular miRNA biosensing. The nanoprobe was composed of NaYF4 :Yb, Er@NaYF4 upconversion nanoparticles (energy donor) with an amino functionalized mesoporous silica shell (NH2 –mSiO2 ), rhodamine B (acceptor) loaded into the mesopores of NH2 –mSiO2, and the complementary sequences of target miRNA (denoted as C-DNA) acting as recognition species wrapped on the nanocomposite. Due to the LRET behavior between donors and acceptors, the loaded rhodamine B can quench the green upconversion emission of NaYF4 :Yb, Er@NaYF4 at 540 nm completely. Moreover, it can be released from the nanocomposite in the presence of target miRNA, which blocked the LRET behavior to "turn on" the green upconversion luminescence. Besides, as the unaffected red upconversion luminescence (at 660 nm) can be used as an internal standard to provide built-in correction for environmental effects, the intensity ratio of upconversion luminescence at 540 and 660 nm ( I 540 / I 660 ) was employed as the output signal to afford an accurate detection of target miRNA. Due to the biocompatibility, high photostability and low auto-fluorescence background, the nanoprobe was successfully utilized to diagnose the intracellular miRNA-21 expression in MCF-7 cells via upconversion fluorescence imaging. We envision that the proposed LBRU nanoprobe has great potential applications in early cancer diagnosis.